Intergenerational Social Mobility in Lithuania: Different Perspectives of Measurement - Vencius, Tautvydas (Socialinė teorija, empirija, politika ir praktika, 2021)
Both scholarly analyses and main political documents have not focused enough on research into social mobility in Lithuania. Such a case is partly understandable as the issue of ensuring social mobility has never been a prevailing one on the political agenda. This article seeks to describe different perspectives on measuring social mobility between generations in Lithuania and to present their empirical expressions. Intergenerational mobility is understood as the difference between the socio-economic situation of parents and adult children, i. y. a comparison of the person’s current circumstances with those from which the person originated. Social positions that can be compared are usually based on occupational, income, education or other social class or socio-economic situation schemes. This article is based on European Social Survey data from wave 9 and reviews the intergenerational social mobility of 1970-1984 generation in terms of education, occupations, income and health dimensions.. The results show that occupational and educational mobility increases between generations. There has been a significant decline in the number of people with only a basic education and at the lowest levels of the occupational scale. However, there is a lack of data on intergenerational social mobility in health and income. Therefore, conclusions about this mobility can only be drawn from the work of previous researchers. Intergenerational mobility can also be a tool to achieve greater economic efficiency. Low intergenerational mobility may mean that some individuals are unable to realize their talents due to their low socio-economic status. Therefore, in the light of the findings of the study, it would make sense to consider developing a social mobility strategy.
Keywords: measurement of social mobility; 1970-1984 generation